2019
DOI: 10.1016/j.matchemphys.2018.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the activities of C2N and BCNO towards Congo red degradation

Abstract: An n-type organic carbon nitride semiconductor, C 2 N, was synthesized by the pyrolysis of uric acid, and its properties were investigated by scanning electron and transmission electron microscopies, X-ray powder diffraction, and vibrational, UV-visible and X-ray photoelectron spectroscopies. This novel material, composed of crystalline flakes, featured a broad absorption centered at 700 nm, possibly due to charge transfer, and a 2.49 eV band gap. Its catalytic performance was assessed for the treatment of eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Therefore, when compared to other CN materials, the significance of C 2 N arises from the fact that the heteroatoms are in a particularly attractive mutual arrangement, and thus, the properties of the collective framework are altered by the concerted action of at least two doping atoms that are jointly active via the para conjugation. We have discussed the influence of this pattern to explain the special performances in gas/water adsorption, [ 37,38 ] catalysis, [ 44 ] and energy storage. [ 40,45–48 ] Furthermore, the pores with six regularly spaced nitrogen lone pairs in the lining ring (N6‐cavities) are extremely suitable for anchoring metallic nanoparticles and single atoms, acting as an “active support.” [ 39–51 ]…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when compared to other CN materials, the significance of C 2 N arises from the fact that the heteroatoms are in a particularly attractive mutual arrangement, and thus, the properties of the collective framework are altered by the concerted action of at least two doping atoms that are jointly active via the para conjugation. We have discussed the influence of this pattern to explain the special performances in gas/water adsorption, [ 37,38 ] catalysis, [ 44 ] and energy storage. [ 40,45–48 ] Furthermore, the pores with six regularly spaced nitrogen lone pairs in the lining ring (N6‐cavities) are extremely suitable for anchoring metallic nanoparticles and single atoms, acting as an “active support.” [ 39–51 ]…”
Section: Introductionmentioning
confidence: 99%
“…As a typical direct azo dye, Congo red (CR) is mainly applied in a relatively large dosage for dyeing biological samples, and can increase the risk of cancer if absorbed into the human body [4]. Currently, there are various industrial methods for treating waste dye solutions, including adsorption, microbial treatment, chemical oxidation or reduction, flocculation precipitation, ozone oxidization, chemical precipitation, nanofiltration, catalytic degradation etcetera [5][6][7]. Due to but also hydrophobic organic oil.…”
Section: Introductionmentioning
confidence: 99%
“…The previous report also concluded that BCNO was photocatalytically inactive towards dye degradation but exhibited an excellent absorbing ability in removing dye from the solution [ 102 ]. The inactive BGH01LT was comprised primarily of tetracoordinate B sites and boron oxides-related bonding.…”
Section: Resultsmentioning
confidence: 99%
“…However, the BGH series comprised the C, and O-doped h-BN domain with various tri-and tetracoordinate boron sites. Interestingly, BGH01 annealed at a lower temperature (Table 1, BGH01LT) was found to be The previous report also concluded that BCNO was photocatalytically inactive towards dye degradation but exhibited an excellent absorbing ability in removing dye from the solution [102]. The inactive BGH01LT was comprised primarily of tetracoordinate B sites and boron oxides-related bonding.…”
Section: Photocatalytic Dye Degradationmentioning
confidence: 89%